QUAL O PAPEL DOS COMPOSTOS QUÍMICOS DOS NINHOS DA VESPA SOCIAL POLISTES VERSICOLOR NO RECONHECIMENTO INTRAESPECÍFICO? - BATISTA, Nathan Rodrigues; DE ARAUJO, Jackson Luiz; NASCIMENTO, Adailton Moraes; GONÇALVES, Welinson Lorenço; DIAS, Rodrigo Leonardo da Silva; ANTONIALLI-JUNIOR, William Fernando (ANAIS DO ENIC, 2017)
-